The Impacts of Crude Oil Market Structure on Stock Market Growth: Evidence from Asian Countries. (30th March 2022) - Le, Hoang Anh; Do, Doan Trang
Abstract : The purpose of this paper is to investigate the impact of crude oil market structure on stock market volatility in Asian countries in the period 2008–2017. We integrate network analysis with the SGMM estimation technique to achieve the research objective. Network analysis was conducted with 43 Asian countries, while analysis of the impact of crude oil market structure on stock markets was performed with a sample of 19 countries. The results show that the stock market has a positive growth in countries with stronger export capacity while it is negatively affected in larger importing countries. In addition, the research results show that the stock market's growth is greater in countries with a central position in the crude oil market. The study results will be useful for countries in reducing the undesirable impact of crude oil market on the stock market.